A phosphorus-carbon composite material, a preparation method and application thereof

CN122968263APending Publication Date: 2026-10-23ORDOS LABORATORY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610699644.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

通常真空封管工艺忽视了“真空度”这一关键变量,导致红磷蒸气的传质过程不可控,极易在孔道口发生浅层填充和堵塞,而非理想的深层均匀填充

Benefits of technology

1、本发明的碳材料具有多孔结构,是以微孔为主、介孔为辅的多级孔结构;其中,碳材料的微孔对磷具有显著的空间限域效应,可以有效抑制磷形成晶态磷,促使其以非晶态或小分子团簇形式存在,从而最大程度缓解磷在充放电过程中的体积膨胀,提升材料的结构稳定性。其中,介孔结构则能够在提供适度限域作用、将磷约束于纳米尺度的同时,为离子输运提供有效通道,有助于实现更高的磷负载量和更快的反应动力学,进而促进容量提升。为保证碳材料的整体机械强度,介孔比例宜控制在10%~20%之间;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968263A_ABST
    Figure CN122968263A_ABST
Patent Text Reader

Abstract

The application provides a phosphorus-carbon composite material and a preparation method and application thereof. The application proposes a dynamic pressure regulation strategy, changes the pressure of the preparation process of the phosphorus-carbon composite material from a fixed value condition to a controllable parameter, realizes the controllable synthesis of phosphorus from static encapsulation to dynamic guidance in the carbon pore channel, and provides a new way for precisely constructing a high-performance phosphorus-carbon negative electrode. In the preparation process of the phosphorus and porous carbon composite material, the pressure in the reactor is regulated in a medium-low vacuum range by adjusting the inert gas flow in the reactor, so as to effectively promote the diffusion and transportation of phosphorus vapor. The method makes the phosphorus vapor not only fully surround the porous carbon particles, avoid shallow filling and pore channel mouth blockage, but also accelerate the deposition process of the phosphorus vapor in the nanopore channel under the driving of moderate pressure, so that more rapid, deeper and more uniform filling is realized, and finally the structure and electrochemical performance of the phosphorus-carbon composite material are optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery anode materials, and specifically relates to a phosphorus-carbon composite material, its preparation method, and its application. Background Technology

[0002] With the accelerating global energy transition, lithium-ion batteries have become dominant in portable electronic devices, electric vehicles, and large-scale energy storage systems. However, their sustainable development faces a series of fundamental challenges. According to relevant survey data, the demand for lithium resources continues to rise with the rapid expansion of the electric vehicle and energy storage markets. To address the challenges of increasingly scarce and costly lithium resources, sodium-ion batteries, based on sodium, an element abundant in the Earth's crust and with low cost, have become an important development direction for next-generation large-scale energy storage.

[0003] However, its commercialization is limited by the performance bottleneck of key anode materials: traditional hard carbon materials (approximately 300 mAh / g) struggle to meet high energy density requirements, while materials such as metal oxides face issues like sluggish kinetics. Red phosphorus, with its ultra-high theoretical capacity of 2596 mAh / g and 0.4 V (vs Na), offers a solution. + The safe operating potential of red phosphorus (significantly higher than the dendrite formation potential) makes it the most promising candidate material. However, two major technical challenges limit its application in sodium-ion batteries. First, the conductivity of pristine amorphous red phosphorus is very low (approximately 10⁻⁶). -14 The volume change of red phosphorus during sodiumification / desodiumification (approximately 300%) leads to severe polarization and low utilization of the active material. Secondly, the volume change is enormous (approximately 300%), resulting in severe pulverization of the active material and loss of electrical contact between the active material and the current collector / conductive additive, thus causing capacity decay.

[0004] To address the aforementioned technical bottlenecks, the research community has widely adopted a strategy of combining porous carbon materials with red phosphorus. Carbon materials possess a high degree of graphitization, which significantly improves the electrical conductivity of the composite material; simultaneously, their three-dimensional porous structure not only provides excellent mechanical support but also effectively suppresses the volume expansion of red phosphorus during cycling through physical confinement. This synergistic effect enables phosphorus-carbon composite materials to possess both high energy density and excellent rate performance.

[0005] Studies have found that red phosphorus has poor dispersibility and binding force. Mechanical ball milling or evaporation-condensation methods cannot effectively allow red phosphorus to enter and remain stably in the micropores of carbon materials, causing red phosphorus to easily detach from the matrix during charging and discharging, resulting in the failure of the active material.

[0006] Furthermore, the loading capacity of red phosphorus is limited. To avoid a sharp decline in performance due to uneven dispersion and volume expansion, existing technologies have to suppress the red phosphorus content to a low level (typically <40 wt%), thus failing to leverage its high theoretical capacity.

[0007] When preparing phosphorus-carbon composites using the evaporation-condensation method, a vacuum sealing process is required. However, this process typically overlooks the crucial variable of "vacuum degree," leading to uncontrollable mass transfer of red phosphorus vapor. This results in shallow filling and blockage at the pore openings, rather than the ideal deep and uniform filling. This is the underlying mechanism causing the poor performance of existing composite materials. Therefore, a method to optimize the uniformity of phosphorus filling within the carbon pores is urgently needed. Summary of the Invention

[0008] This invention addresses the aforementioned problems in existing technologies by proposing a phosphorus-carbon composite material, its preparation method, and its applications. Researchers discovered that the vacuum level of the reaction environment is a frequently overlooked but crucial process parameter in the preparation of phosphorus-carbon composite materials via the evaporation-condensation method. This invention systematically analyzes and predicts the transport patterns of red phosphorus vapor under different vacuum levels, such as from high vacuum to medium-low vacuum and then to low pressure, as well as the filling behavior within various porous carbon nanopores, including zeolite-templated carbon, coconut shell carbon, and phenolic resin carbon, and the differences in the microstructure of the final composite material. This invention proposes that by simultaneously and continuously evacuating the reactor and introducing a controllable flow rate of inert gas, the total system pressure and the partial pressure of red phosphorus vapor can be synergistically controlled. Studies indicate that under high vacuum, red phosphorus is transported in a molecular flow mode, easily leading to shallow filling and pore blockage; however, by precisely controlling the reaction environment within the medium-low vacuum range, red phosphorus vapor can be induced to be transported in a viscous flow and diffusion mode, thereby achieving deep and uniform deposition within the pores of the zeolite-templated carbon. Therefore, the phosphorus-carbon composite material with the optimized structure of this invention is expected to serve as a negative electrode for sodium-ion batteries, while exhibiting high reversible capacity and excellent cycle stability.

[0009] This invention reveals that vacuum level is a key factor controlling phosphorus filling behavior. It elucidates for the first time that high vacuum causes red phosphorus vapor to be transported in a molecular flow mode. Under this mechanism, phosphorus molecules move in a straight line, and their trajectories are highly directional, causing their deposition in the carbon matrix to be heavily dependent on spatial position. Therefore, non-selective accumulation easily occurs at the pore inlet, forming a "blocking effect," which not only significantly limits the effective phosphorus loading but also hinders its diffusion into the deeper layers of the internal micropores, ultimately resulting in uneven distribution of active materials and low utilization of pore space.

[0010] Therefore, based on the above mechanism, this invention proposes a dynamic pressure control strategy. This method transforms pressure from a fixed condition into an adjustable parameter, achieving a leap from "static encapsulation" to "dynamic guidance" for controllable synthesis, and providing a new approach for the precise construction of high-performance phosphorus-carbon anodes.

[0011] In one aspect, the present invention provides a phosphorus-carbon composite material comprising phosphorus and carbon, wherein the mass percentage of phosphorus is 25 wt% to 88 wt% and the mass percentage of carbon is 12 wt% to 75 wt%.

[0012] In one or more embodiments, the phosphorus-carbon composite material includes mesopores and optionally present micropores, wherein the micropore volume accounts for 0% to 25% of the total pore volume and the mesopore volume accounts for 75% to 100% of the total pore volume.

[0013] In one or more embodiments, the specific surface area of ​​the phosphorus-carbon composite material is ≥70 m². 2 / g, for example 70-120 m 2 / g.

[0014] In another aspect, the present invention provides a method for preparing a phosphorus-carbon composite material.

[0015] In one or more implementations, the method includes the following steps: (1) Add carbon materials and phosphorus into the reactor and evacuate the reactor to the first vacuum level; (2) Inject protective gas into the reactor to the second vacuum level; (3) Heat the reactor to the first temperature to evaporate the phosphorus; (4) The material is kept at a first temperature for a first time, and then kept at a second temperature for a second time, so that phosphorus is deposited on the surface and in the pores of the carbon material to obtain the deposited product.

[0016] In one or more embodiments, in step (1), the carbon material is selected from one or more of zeolite template carbon, carbon nanotubes, coconut shell carbon, and phenolic resin hard carbon.

[0017] In one or more embodiments, in step (1), the volume percentage of micropores in the pore structure of the carbon material is 80% to 90%, and the volume percentage of mesopores is 10% to 20%.

[0018] In one or more embodiments, in step (1), the phosphorus is red phosphorus, which can be selected from commonly used red phosphorus in the art. The red phosphorus of this invention was purchased from Maclean Biotechnology Co., Ltd.

[0019] In one or more embodiments, in step (1), the mass ratio of carbon material to phosphorus is 1:0.3 to 1:8.

[0020] In one or more embodiments, in step (1), the reactor is a high-temperature resistant tube, preferably a high borosilicate glass tube, a quartz glass tube, an aluminosilicate glass tube, or a high-purity alumina tube.

[0021] In one or more embodiments, in step (1), the first vacuum degree is a relative vacuum degree of -0.1 to 0 MPa.

[0022] In one or more embodiments, in step (2), the protective gas is argon or nitrogen.

[0023] In one or more embodiments, in step (2), the second vacuum degree is a relative vacuum degree of -0.1 to 0.2 MPa.

[0024] In one or more embodiments, the second vacuum degree is greater than the first vacuum degree.

[0025] In one or more embodiments, in step (3), the heating rate to the first temperature is 2~5℃ / min, and the first temperature is 400℃~700℃.

[0026] In one or more implementations, in step (4), the first time is 1 h to 10 h.

[0027] In one or more embodiments, in step (4), the second temperature is 200°C to 300°C.

[0028] In one or more embodiments, in step (4), the second time is 10 to 30 hours.

[0029] In one or more embodiments, step (4) further includes: after holding at the second temperature for a second time, naturally cooling to room temperature.

[0030] In one or more embodiments, the method further includes a cleaning step, which involves cleaning the deposited product obtained in step (4) with a cleaning solution and then drying it; wherein the cleaning solution is one of NaOH solution, dilute nitric acid and CS2, wherein the concentration of NaOH in the NaOH solution is 1 mol / L to 3 mol / L, and the mass fraction of nitric acid in the dilute nitric acid is 5% to 10%.

[0031] In this invention, step (1) of the method for preparing zeolite template carbon includes the following steps: (1') Pretreatment of zeolite molecular sieves; (2') Carbon is deposited on zeolite molecular sieves by vapor deposition; (3') Acid washing removes zeolite molecular sieves to obtain zeolite template carbon.

[0032] In one or more embodiments, in step (1'), the zeolite molecular sieve (ZTC) is selected from one of Y-type zeolite, β-type zeolite, LTA-type zeolite, and ZSM-5 zeolite. In this invention, the zeolite molecular sieve can be a commonly used zeolite molecular sieve in the art; for example, the Y-type zeolite can be commercial zeolite NaY powder (crystal size <6 μm, Si / Al molar ratio = 5~12), purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.

[0033] In one or more embodiments, in step (1'), the pretreatment of the zeolite molecular sieve is to heat it to 200°C to 400°C under an inert atmosphere, the inert atmosphere being nitrogen or argon, for a heating time of 1 to 10 h.

[0034] In one or more embodiments, step (2') of vapor deposition comprises two stages. The first stage involves heating to 500°C to 800°C at a rate of 5°C / min in a mixed atmosphere of 10 to 70 sccm of carbon source gas and 20 to 70 sccm of protective gas for 1 to 10 h. The carbon source gas is one of methane, ethylene, propylene, and acetylene. The protective gas is selected from nitrogen, argon, and an argon / hydrogen mixture, wherein the argon / hydrogen mixture is 2% VOL to 5% VOL of H2 and 95% VOL to 98% VOL of argon.

[0035] In one or more embodiments, in step (2'), the second stage of vapor deposition is switched to a protective gas, which is heated to 700°C~1200°C at 5°C / min for 1~10 h. The protective gas is selected from nitrogen, argon and argon / hydrogen mixture, wherein the argon / hydrogen mixture is 2%VOL~5%VOL H2 and 95%VOL~98%VOL argon.

[0036] In one or more embodiments, in step (3'), the zeolite template is washed away by a mixed solution of 50-200 mL of 0.1-1 M HF and 50-200 mL of 0.1-1 M HCl to obtain zeolite template carbon ZTC.

[0037] In another aspect, the present invention provides a battery negative electrode or sodium-ion battery comprising the phosphorus-carbon composite material described in any one of the present invention or the phosphorus-carbon composite material obtained by the method described in any one of the present invention.

[0038] In another aspect, the present invention provides the following applications: (1) The application of the method described in any one of the present invention in improving the uniformity of phosphorus filling in the pores of carbon materials; (2) The application of the phosphorus-carbon composite material described in any one of the present invention or the phosphorus-carbon composite material obtained by the method described in any one of the present invention in improving battery capacity and / or cycle stability. Attached Figure Description

[0039] Figure 1 This is a schematic diagram of the preparation method according to an embodiment of the present invention; Figure 2 (a) Nitrogen adsorption / desorption isotherm and (b) pore size distribution curve of the phosphorus-carbon composite material prepared in Example 1; Figure 3 SEM image of the phosphorus-carbon composite material prepared in Example 1; Figure 4 The XRD pattern of the phosphorus-carbon composite material prepared in Example 1; Figure 5 The charge-discharge curves of the half-cell assembled from the phosphorus-carbon composite material prepared in Example 1 during the first week are shown. Detailed Implementation

[0040] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used herein are explained and defined in general terms below. Unless otherwise specified, all technical and scientific terms used herein have the common meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0041] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0042] In this document, the terms “contains,” “includes,” “containing,” and similar terms encompass the meanings of “basically composed of” and “composed of.” For example, when this document discloses “A contains B and C,” “A is basically composed of B and C” and “A is composed of B and C” should be considered as having been disclosed in this document.

[0043] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0044] Unless otherwise specified, percentages refer to mass percentages and proportions refer to mass ratios in this article.

[0045] In this article, the sum of the percentages of all components in the composition is 100%.

[0046] In this document, when describing embodiments or examples, it should be understood that it is not intended to limit the invention to those embodiments or examples. Rather, all alternatives, modifications, and equivalents of the methods and materials described herein are covered within the scope of this invention.

[0047] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0048] Phosphorus-carbon composite materials

[0049] In this invention, the phosphorus-carbon composite material contains phosphorus and carbon. The mass percentage of phosphorus is 25 wt% to 88 wt%, for example, 25 wt%, 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 51 wt%, 52 wt%, 55 wt%, 57 wt%, 59 wt%, 60 wt%, 62.5%, 65 wt%, 70 wt%, 75 wt%, 80 wt%, 85 wt%, 88 wt%. The mass percentage of carbon is 12 wt% to 75 wt%, for example, 12 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, 35 wt%, 37.5 wt%, 40 wt%, 41 wt%, 43 wt%, 45 wt%, 48 wt%, 49 wt%, 50 wt%, 55 wt%, 60 wt%, 62.5%, 65 wt%, 70 wt%, 75 wt%.

[0050] In this invention, the phosphorus-carbon composite material comprises mesopores and optionally micropores, wherein the micropore volume accounts for 0% to 25% of the total pore volume, for example, 0%, 2%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 17%, 18%, 20%, 22%, 24%, 25%, and the mesopore volume accounts for 75% to 100% of the total pore volume, for example, 75%, 76%, 78%, 80%, 83%, 85%, 90%, 95%, 100%. Phosphorus effectively fills the numerous microporous structures of carbon while retaining the mesoporous structure.

[0051] In this invention, the pore size of the micropores is 0~2 nm, and the pore size of the mesopores is 2~50 nm.

[0052] In this invention, the specific surface area of ​​the phosphorus-carbon composite material is ≥70 m². 2 / g, for example 70-120 m 2 / g, can be 70 m2 / g, 74.45 m 2 / g、80 m 2 / g、88.12 m 2 / g、90 m 2 / g, 92.37 m 2 / g、100 m 2 / g, 103.33 m 2 / g、110 m 2 / g、120 m 2 / g.

[0053] Preparation method of phosphorus-carbon composite material

[0054] The preparation method of the phosphorus-carbon composite material of the present invention includes the following steps: (1) Add carbon materials and phosphorus into the reactor and evacuate the reactor to the first vacuum level; (2) Inject protective gas into the reactor to a second vacuum level; (3) Heat the reactor to the first temperature to evaporate the phosphorus; (4) The material is kept at a first temperature for a first time, and then kept at a second temperature for a second time, so that phosphorus is deposited on the surface and pores of the carbon material to obtain the deposited product.

[0055] In this invention, in step (1), the carbon material is selected from one or more of zeolite template carbon, carbon nanotubes, coconut shell carbon, and phenolic resin hard carbon.

[0056] In this invention, in step (1), the volume ratio of micropores in the pore structure of carbon material is 80%~90%, such as 80%, 82%, 85%, 86%, 88%, 89%, 90%, and the volume ratio of mesopores is 10%~20%, such as 10%, 12%, 15%, 18%, 19%, 20%.

[0057] In this invention, in step (1), the phosphorus is red phosphorus, which can be any type of red phosphorus commonly used in the art. The red phosphorus used in this invention was purchased from Maclean Biotechnology Co., Ltd.

[0058] In this invention, in step (1), the mass ratio of carbon material to phosphorus is 1:0.3 to 1:8, for example, 1:0.3, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8.

[0059] In this invention, in step (1), the reactor is a high-temperature resistant tube, preferably a high borosilicate glass tube, a quartz glass tube, an aluminosilicate glass tube, or a high-purity alumina tube.

[0060] In this invention, in step (1), the first vacuum degree is a relative vacuum degree of -0.1~0 MPa, for example -0.1 MPa, -0.09 MPa, -0.07 MPa, -0.05 MPa, or 0 MPa.

[0061] In this invention, the pressure inside the reactor is controlled within a low to medium vacuum range (i.e., a first vacuum level) by evacuation, and the flow rate of the protective gas is adjusted accordingly to maintain a certain total pressure environment within the reactor. This allows phosphorus vapor to be transported within the porous carbon channels in a combination of viscous and diffused flow patterns. This pressure environment not only effectively avoids shallow filling and pore blockage caused by molecular flow under high vacuum conditions, but also effectively promotes the diffusion and transport of phosphorus vapor by moderately increasing the driving force of gas phase transport. Under these conditions, phosphorus vapor can not only fully surround the porous carbon particles, but also accelerate its deposition process within the nanopores under moderate pressure, thereby achieving faster, deeper, and more uniform filling.

[0062] In this invention, in step (2), the protective gas is argon or nitrogen.

[0063] In this invention, in step (2), the second vacuum degree is a relative vacuum degree of -0.1~0.2 MPa, such as -0.1 MPa, -0.09 MPa, -0.07 MPa, -0.05 MPa, -0.03 MPa, 0 MPa, 0.05 MPa, 0.1 MPa, 0.15 MPa, 0.2 MPa.

[0064] In this invention, the first vacuum degree is the relative vacuum degree measured by evacuating the reactor, and the second vacuum degree is the relative vacuum degree measured after introducing a protective gas into the evacuated reactor.

[0065] In this invention, the second vacuum degree is greater than the first vacuum degree.

[0066] In this invention, in step (3), the heating rate to the first temperature is 2~5℃ / min, for example 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min; the first temperature is 400℃~700℃, for example 400℃, 500℃, 600℃, 700℃.

[0067] In this invention, in step (4), the first time is 1 h to 10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h.

[0068] In this invention, in step (4), the second temperature is 200℃~300℃, such as 200℃, 220℃, 250℃, 280℃, or 300℃.

[0069] In this invention, in step (4), the second time is 10~30 h, for example 10 h, 15 h, 20 h, 25 h, 30 h.

[0070] In this invention, step (4) further includes: after holding at the second temperature for a second time, naturally cooling to room temperature.

[0071] In this invention, the vapor partial pressure of red phosphorus is adjusted by controlling the heating temperature in step (3). The temperature range is 400℃~700℃. Inside the encapsulated reactor, red phosphorus sublimates upon heating, generating red phosphorus vapor partial pressure, which ranges from 42.6 Pa to 20.4 kPa. The total pressure inside the reactor is the sum of the initial system pressure and the red phosphorus vapor partial pressure. Depending on the heating temperature, both the red phosphorus vapor partial pressure and the total pressure inside the reactor change. When there is no heating, such as at room temperature, the initial system pressure and total pressure inside the reactor are directly measured and displayed by a vacuum pressure gauge or pressure sensor connected to the reactor, showing the relative vacuum level. After heating, the vapor partial pressure of red phosphorus is the saturated vapor pressure of red phosphorus at that heating temperature. The vapor partial pressure of red phosphorus is only related to the heating temperature of red phosphorus and is independent of the reactor volume, the amount of red phosphorus used, and the system pressure.

[0072] In this invention, the method further includes a cleaning step, which involves cleaning the deposited product obtained in step (4) with a cleaning solution and then drying it. The cleaning solution is one of NaOH solution, dilute nitric acid, and CS2. The concentration of NaOH in the NaOH solution is 1 mol / L to 3 mol / L. The mass fraction of nitric acid in the dilute nitric acid is 5% to 10%. The cleaning solution can wash away excess white phosphorus and red phosphorus.

[0073] In this invention, step (1) of the method for preparing zeolite template carbon includes the following steps: (1') Pretreatment of zeolite molecular sieves; (2') Carbon is deposited on zeolite molecular sieves by vapor deposition; (3') Acid washing removes zeolite molecular sieves to obtain zeolite template carbon.

[0074] In this invention, in step (1'), the zeolite molecular sieve (ZTC) is selected from one of Y-type zeolite, β-type zeolite, LTA-type zeolite, and ZSM-5 zeolite. In this invention, the zeolite molecular sieve can be a commonly used zeolite molecular sieve in the art; for example, the Y-type zeolite can be commercial zeolite NaY powder (crystal size <6 μm, Si / Al molar ratio = 5~12), purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.

[0075] In this invention, in step (1'), the pretreatment of zeolite molecular sieve is carried out by heating to 200℃~400℃ in an inert atmosphere, the inert atmosphere being nitrogen or argon, the heating temperature being 200℃, 300℃, or 400℃, and the heating time being 1~10 h, which can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h.

[0076] In this invention, step (2') involves two stages of vapor deposition. The first stage involves heating to 500°C–800°C at a rate of 5°C / min in a mixed atmosphere of 10–70 sccm carbon source gas and 20–70 sccm protective gas for 1–10 h. The carbon source gas is one of methane, ethylene, propylene, and acetylene. The flow rate of the carbon source gas can be 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, or 70 sccm. The protective gas is selected from nitrogen, argon, and an argon / hydrogen mixture. The argon / hydrogen mixture consists of 2% VOL–5% VOL H2 and 95% VOL–98% VOL argon. The flow rate of the protective gas can be 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, or 70 sccm. sccm; the heating temperature can be 500℃, 600℃, 700℃, or 800℃; the heating time can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h; The second stage involves switching to a protective gas and heating at 5 °C / min to 700 °C~1200 °C for 1~10 h. The protective gas is selected from nitrogen, argon, and an argon / hydrogen mixture. The argon / hydrogen mixture consists of 2% VOL~5% VOL H2 and 95% VOL~98% VOL argon. The heating temperature can be 700 °C, 800 °C, 900 °C, 1000 °C, 1100 °C, or 1200 °C, and the heating time can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or 10 h.

[0077] In this invention, when the protective gas is a hydrogen / argon mixture, the formation of tar or carbon deposits during the pyrolysis of carbon materials can be suppressed, promoting the ordering of carbon and increasing the degree of graphitization; by pyrolyzing and gasifying some amorphous carbon, the microporosity of carbon materials is increased.

[0078] In this invention, in step (3'), the acid washing uses a mixed solution of 50-200 mL of 0.1-1 M HF and 50-200 mL of 0.1-1 M HCl to wash away the zeolite template and obtain zeolite template carbon ZTC; wherein, the concentration of the HF solution can be 0.1 M, 0.3 M, 0.5 M, 0.7 M, or 1 M, and the volume can be 50 mL, 100 mL, 150 mL, or 200 mL; the concentration of the HCl solution can be 0.1 M, 0.3 M, 0.5 M, 0.7 M, or 1 M, and the volume can be 50 mL, 100 mL, 150 mL, or 200 mL.

[0079] application

[0080] A battery negative electrode or sodium-ion battery comprising a phosphorus-carbon composite material according to any embodiment of the present invention or a phosphorus-carbon composite material obtained by the preparation method according to any embodiment of the present invention.

[0081] The application of the preparation method of any embodiment of the present invention in improving the uniformity of phosphorus filling in carbon channels.

[0082] The application of the phosphorus-carbon composite material of any embodiment of the present invention or the phosphorus-carbon composite material obtained by the preparation method of any embodiment of the present invention in improving battery capacity and / or cycle stability.

[0083] Sodium-ion batteries

[0084] Sodium-ion batteries include half-cells and full-cells.

[0085] In this aspect, the half-cell sodium-ion battery includes a negative electrode, a counter electrode, and an electrolyte. The negative electrode material of the half-cell is a phosphorus-carbon composite material prepared by the method of any embodiment of this invention. The counter electrode of the half-cell can be metallic sodium or layered transition metal oxides (such as Na₂O₃). x CoO2), polyanionic compounds (such as Na3V2(PO4)3), or Prussian blue analogues (such as Na2Fe[Fe(CN)6]). The assembly of this battery includes, in sequence: lower casing, counter electrode, separator, negative electrode, electrolyte, spring contact, gasket, and upper casing. The upper and lower casings of the half-cell, such as those of a button cell, are commonly used in this field, such as a 304 circular grooved casing. The electrolyte for the half-cell is commonly NaPF6 or NaClO4 dissolved in a carbonate solvent at a concentration of 1M; the separator needs to have high alkali resistance and porosity (>40%).

[0086] In the present invention, the full-cell sodium-ion battery comprises a housing, a cell, a cover plate for encapsulating the housing, and an electrolyte located inside the housing and between the cells. The cell comprises a positive electrode sheet, a negative electrode sheet, and a separator located between the positive and negative electrode sheets. The positive and negative electrode sheets respectively comprise positive and negative current collectors and positive and negative electrode materials coated on the current collectors. Wherein, the negative electrode material comprises the phosphorus-carbon composite material of the present invention. The negative electrode material further includes a binder, a conductive agent and the like, and may also contain additives and the like. The negative electrode sheet is prepared by various methods well known to those skilled in the art, for example, the negative electrode active material of the present invention is dissolved in a solvent in a certain ratio with a binder, a conductive agent, an additive and the like to be mixed into a negative electrode slurry, then the negative electrode slurry is coated on a wide negative electrode current collector, followed by drying, rolling and slitting to obtain the negative electrode sheet. Wherein, the binder is various substances commonly used in the art, selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The additive may be sodium carboxymethyl cellulose (CMC-Na) and the like.

[0087] The cell structure of the battery provided by the present invention is a cell structure commonly used in the art. Generally, the cell can be prepared by winding or stacking the positive electrode sheet, the separator and the negative electrode sheet, and the winding or stacking manner is well known to those skilled in the art.

[0088] The positive electrode material of the present invention is not particularly limited, and the positive electrode material generally includes a positive electrode active substance, a binder and a conductive agent. The positive electrode active substance may include sodium transition metal oxides, polyanionic compounds, Prussian blue-based compounds and the like, but the present application is not limited to these materials, and other conventionally known materials that can be used as the positive electrode active material for sodium-ion batteries may also be used. Wherein, in the sodium transition metal oxide, the transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce. The sodium transition metal oxide is, for example, Na x MO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr and Cu, and 0<x≤1. Wherein, the polyanionic compound may be a type of compound having sodium ions, transition metal ions and tetrahedral (YO4) n- anion units. The transition metal may be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr and Ce; Y may be at least one of P, S and Si; n represents (YO4) n-The valence state. Among them, polyanionic compounds include, for example, NaFePO4, Na3V2(PO4)3, NaM'PO4F (M' is one or more of V, Fe, Mn and Ni) and Na3(VO y )2(PO4)2F 3-2y At least one of (0≤y≤1). Prussian blue compounds can contain sodium ions, transition metal ions, and cyanide ions (CN). - A class of compounds. The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na. a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co, and Zn, 0 <a≤2,0<b<1,0<c<1。

[0089] The binder in the cathode material can be any binder known in the art, including at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resins. The conductive agent in the cathode material can be at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0090] In this invention, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0091] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This invention does not impose specific limitations on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel-like, or entirely solid. The electrolyte of this invention is an electrolyte solution comprising an electrolyte salt and a solvent. The electrolyte salt can be selected from at least one of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate, sodium hexafluoroarsenate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium difluorophosphate, sodium difluorooxalate borate, sodium di(oxalate borate), sodium di(oxalate phosphate), and sodium tetrafluorooxalate phosphate. The solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0092] In this invention, the full battery also includes a separator. This invention does not impose any particular limitation on the type of separator; porous separators with good chemical and mechanical stability known to those skilled in the art can be selected, such as at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0093] In this invention, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly through a winding process or a stacking process.

[0094] The positive current collector and negative current collector of the present invention are not particularly limited, and various positive current collectors and negative current collectors known to those skilled in the art can be used, which will not be described again.

[0095] The present invention has the following beneficial effects: 1. The carbon material of this invention has a porous structure, which is a hierarchical porous structure dominated by micropores and supplemented by mesopores. The micropores of the carbon material have a significant spatial confinement effect on phosphorus, effectively inhibiting the formation of crystalline phosphorus and promoting its existence in amorphous or small molecular clusters, thereby minimizing the volume expansion of phosphorus during charging and discharging and improving the structural stability of the material. The mesoporous structure, while providing moderate confinement and limiting phosphorus to the nanoscale, also provides effective channels for ion transport, contributing to higher phosphorus loading and faster reaction kinetics, thus promoting capacity improvement. To ensure the overall mechanical strength of the carbon material, the mesoporous ratio should preferably be controlled between 10% and 20%. 2. To achieve uniform phosphorus distribution within the pores of carbon materials, this invention designs an environment for the phosphorus-carbon composite reaction that is precisely controlled within a medium-to-low vacuum range. By synergistically adjusting the total system pressure and the partial pressure of phosphorus vapor, phosphorus vapor can be transported within the porous carbon channels using a combination of viscous and diffuse flow. This medium-to-low pressure environment effectively avoids shallow filling and pore blockage caused by molecular flow under high vacuum conditions. Furthermore, by moderately increasing the driving force of gas-phase transport, it accelerates the transport and deposition of phosphorus vapor in the porous medium, thereby achieving deeper, more uniform, and more efficient filling within the nanopores.

[0096] The present invention will be described below by way of specific embodiments. It should be understood that these embodiments are merely illustrative and are not intended to limit the scope of the invention. The methods, reagents, and materials used in the embodiments and comparative examples are conventional methods, reagents, and materials in the art, unless otherwise stated. The starting material compounds in the embodiments and comparative examples are all commercially available.

[0097] Test Example 1

[0098] Scanning electron microscope (SEM) images

[0099] The microstructure of phosphorus-carbon composite powder was imaged using a Thermo Fisher Verios 5UC field emission scanning electron microscope.

[0100] Test Example 2

[0101] X-ray diffraction (XRD) patterns

[0102] The material structure of phosphorus-carbon composite powder was analyzed using a D8 25X X-ray photoelectron spectrometer (Bruker, Germany).

[0103] Test Example 3

[0104] Charge-discharge performance test of sodium-ion half-cell

[0105] Using metallic sodium as the counter electrode, a voltage of 0.1 A g was applied within the range of 0.05–1.5 V. -1 The current density was tested on the half-cell.

[0106] Test Example 4

[0107] Pore ​​volume of carbon materials, specific surface area and pore volume of phosphorus-carbon composites.

[0108] The pore volume of carbon materials and the specific surface area and pore volume of phosphorus-carbon composite materials were tested using a high-vacuum physical adsorption analyzer (model: Autosorb 6100).

[0109] Example 1

[0110] Chemical vapor deposition (CVD) was used to prepare template carbon for molecular sieves. Y-type zeolite molecular sieves were used as templates. The zeolite molecular sieves were pretreated, followed by CVD, and then acid washing to obtain the zeolite template carbon. The pretreatment process was carried out under an argon atmosphere at 200℃ for 4 h. The first stage of CVD was performed in a mixed atmosphere of 30 sccm ethylene and 30 sccm argon, with a heating rate of 5℃ / min to 500℃ for 2 h. The second stage was performed under an argon atmosphere, with a heating rate of 5℃ / min to 800℃ for 3 h. Acid washing was performed using a mixed solution of 50 mL 0.5 M HF and 50 mL 0.5 M HCl to remove the zeolite template. The resulting carbon material sample was designated ZTC-Y, with a mesoporous volume fraction of 18%.

[0111] Preparation of red phosphorus-zeolite template carbon composite material by evaporation-condensation method: 50 parts by mass of red phosphorus and 30 parts by mass of zeolite template carbon were sealed in a vacuum-sealed glass tube with a first vacuum degree of -0.09 MPa. The sealed glass tube was then heated to a second vacuum degree of -0.07 MPa under an Ar gas flow; the temperature was increased to 500℃ at a heating rate of 4℃ / min and held for 2 h, then cooled to 260℃ and held for 20 h, and finally allowed to cool naturally to room temperature. The resulting phosphorus-carbon sample was stirred in CS2 for 3 h and dried in a vacuum oven at 60℃. The resulting sample was denoted as P / C-0.07, with a carbon content of 43 wt% and a phosphorus content of 57 wt%.

[0112] Example 2

[0113] The difference from Example 1 is that in the preparation of the phosphorus-carbon composite material by the evaporation-condensation method, red phosphorus and carbon materials are encapsulated in a vacuum-sealed glass tube with a first vacuum degree of -0.09 MPa. The sealed vacuum-sealed glass tube is then subjected to an Ar gas flow to achieve a second vacuum degree of -0.02 MPa. Other preparation methods are the same as in Example 1. The obtained sample is denoted as P / C-0.02, wherein the carbon content is 48 wt% and the phosphorus content is 52 wt%.

[0114] Example 3

[0115] The difference from Example 1 is that in the preparation of the phosphorus-carbon composite material by the evaporation-condensation method, red phosphorus and carbon materials are encapsulated in a vacuum-sealed glass tube with a first vacuum degree of -0.1 MPa. The sealed vacuum-sealed glass tube is then subjected to an Ar gas flow to achieve a second vacuum degree of -0.09 MPa. Other preparation methods are the same as in Example 1. The obtained sample is denoted as P / C-0.09, wherein the carbon content is 41 wt% and the phosphorus content is 59 wt%.

[0116] Example 4

[0117] The difference from Example 1 is that the carbon material is carbon nanotubes with a mesopore volume ratio of 19%, and the step of preparing zeolite molecular sieve template carbon is not included; other conditions are the same as in Example 1. The resulting sample contains 49 wt% carbon and 51 wt% phosphorus.

[0118] Comparative Example 1

[0119] The difference from Example 1 is that in the preparation of the phosphorus-carbon composite material by the evaporation-condensation method, red phosphorus and carbon materials are encapsulated in a vacuum-sealed glass tube with a first vacuum degree of -0.1 MPa. The sealed vacuum-sealed glass tube is then subjected to an Ar gas flow to achieve a second vacuum degree of 0.3 MPa. The resulting sample contains 74 wt% carbon and 26 wt% phosphorus.

[0120] Comparative Example 2

[0121] The difference from Example 1 is that in the preparation of the phosphorus-carbon composite material by the evaporation-condensation method, red phosphorus and carbon materials are encapsulated in a vacuum-sealed glass tube with a first vacuum degree of -0.1 MPa. The sealed vacuum-sealed glass tube is then subjected to an Ar gas flow to achieve a second vacuum degree of 0.4 MPa. The resulting sample contains 83 wt% carbon and 17 wt% phosphorus.

[0122] Comparative Example 3

[0123] The difference from Example 1 is that ordinary carbon powder was selected as the carbon material, with a mesoporous volume ratio of 40% and a macroporous volume ratio of approximately 30%. Other preparation conditions were the same as in Example 1. The resulting sample contained 76 wt% carbon and 24 wt% phosphorus.

[0124] Preparation Example 1

[0125] This preparation example provides a method for preparing an electrode containing a phosphorus-carbon composite material.

[0126] The phosphorus-carbon composite materials prepared in Examples 1-4 and Comparative Examples 1-3 were mixed with sodium alginate (SA) and carbon nanotubes at a mass ratio of 8:1:1 to prepare a slurry using water as a solvent. After thorough mixing, the slurry was uniformly coated onto copper foil. The mixture was dried in a vacuum drying oven at 110°C for 5 hours, cut into circular electrode sheets with a diameter of 16 mm, numbered, weighed, and then transferred to an argon-filled glove box for battery assembly.

[0127] Preparation Example 2

[0128] This preparation example provides a method for assembling a battery including the electrode of Preparation Example 1.

[0129] CR2032 coin cell half-cells were assembled in an argon-filled glove box. A 16 mm diameter circular electrode obtained in Preparation Example 1 was used as the working electrode of the sodium-ion battery, with a sodium sheet as the counter electrode. GF / D type glass fiber was used as the separator, and a 1M NaClO4 solution was used as the electrolyte. The electrolyte solvent included EC and DEC in a 1:1 mass ratio, and also included 5% FEC by mass of the total electrolyte solvent. During battery assembly, the concentrations of O2 and H2O in the glove box should be kept below 0.1 ppm, and insulated tweezers should be used to prevent short circuits. The cells were assembled in the following order: positive electrode shell, negative electrode sheet, separator, 0.8 μL electrolyte, sodium sheet, gasket, spring contact, and negative electrode shell. Finally, the assembled cells were pressed together using a battery packaging machine. Electrochemical performance tests were performed after standing for 12 h.

[0130] The specific surface area, mesoporous volume ratio, and initial and reversible discharge specific capacity and first coulombic efficiency of the phosphorus-carbon composite materials prepared in Examples 1-4 and Comparative Examples 1-3 are summarized in Table 1.

[0131] Table 1

[0132] As shown in Table 1, the phosphorus-carbon composite materials of Examples 1-4 of this invention have a high specific surface area, reaching 74.45 m². 2 The phosphorus-carbon composite material prepared in Comparative Examples 1-3 had a low specific surface area and a low mesoporous volume ratio (53%-68%), indicating that the micropores accounted for a relatively low proportion and the pore structure was mainly mesoporous. This is because phosphorus effectively and uniformly filled the micropores in the carbon material, thus preserving the mesopores. In contrast, the phosphorus-carbon composite materials prepared in Comparative Examples 1-3 had a very low specific surface area and a low mesopore volume ratio (53%-68%), indicating that the volume ratio of micropores and mesoporous structures in the phosphorus-carbon composite materials of Comparative Examples 1-3 was not high. It is possible that the macroporous structure provided the specific surface area, resulting in a low specific surface area. Therefore, the quality of phosphorus filling inside the micropore channels of the carbon material was also low, and effective phosphorus filling could not be achieved.

[0133] Furthermore, the initial discharge specific capacity and reversible discharge specific capacity of the half-cell containing the phosphorus-carbon composite materials of Examples 1-4 of the present invention reach 1183.24 mAh g⁻¹. -1 and 960.52 mAh g -1 The initial coulombic efficiency is above 80.56%, significantly higher than the half-cell performance of the phosphorus-carbon composite materials containing Comparative Examples 1-3. The test results indicate that phosphorus in the phosphorus-carbon composite material of this invention fills the carbon channels more uniformly, significantly improving the battery's electrochemical performance, such as battery capacity and cycle stability.

[0134] Figure 2(a) Nitrogen adsorption / desorption isotherms and (b) pore size distribution curves of the phosphorus-carbon composite material prepared in Example 1 are shown. As can be seen from the figures, the phosphorus-carbon composite material of Example 1 exhibits typical Type IV characteristics and shows a hysteresis loop in the P / P0 = 0.1-1.0 range. The pore size distribution curves show that the composite material possesses both microporous and mesoporous structures, with a higher proportion of mesoporous volume, indicating that phosphorus effectively fills the microporous structure in the carbon matrix. The specific surface area of ​​the phosphorus-carbon composite material is 88.12 m². 2 g -1 The pore volume is 0.09 cm³. 3 g -1 .

[0135] Figure 3 The image shows a SEM image of the phosphorus-carbon composite material prepared in Example 1. SEM analysis shows that there is no obvious phosphorus agglomeration on the surface of the phosphorus-carbon composite material, indicating that under vacuum conditions, phosphorus was deposited deeply and uniformly within the carbon channels of the zeolite template.

[0136] X-ray diffraction (XRD) characterization results are as follows Figure 4 As shown, for the phosphorus-carbon composite material, characteristic broad peaks of amorphous carbon were observed at 2θ = 25.9° (002 crystal plane) and 2θ = 43.5° (100 crystal plane). Notably, the phosphorus-carbon composite material retained the characteristic diffraction peak of phosphorus at 2θ = 15°, and all diffraction peaks could be attributed to the linear superposition of the carbon framework and phosphorus diffraction, with no characteristic peaks of other crystalline impurities detected. This result confirms from a crystallographic perspective that the evaporation-condensation process achieved physical dispersion of phosphorus in the carbon matrix without initiating a phosphorus-carbon chemical reaction or the formation of a new phase.

[0137] A constant current charge-discharge test method was used, with metallic sodium as the counter electrode, and the charge-discharge rate was 0.1 A g within a voltage range of 0.05~1.5 V. -1 Current density was tested on the half-cell. For example... Figure 5 As shown, the initial discharge specific capacity of the phosphorus-carbon composite electrode prepared in Example 1 is 1229.03 mAh g. -1 The reversible specific capacity during the first charge is 1027.96 mAh g. -1 The initial coulombic efficiency was 83.64%. Compared to the phosphorus electrode, the composite material showed significantly improved cycle stability.

Claims

1. A phosphorus-carbon composite material, characterized in that, The phosphorus-carbon composite material contains phosphorus and carbon, with phosphorus accounting for 25 wt% to 88 wt% by mass and carbon accounting for 12 wt% to 75 wt% by mass. The phosphorus-carbon composite material comprises mesopores and optionally micropores, wherein the volume of micropores accounts for 0% to 25% of the total pore volume, and the volume of mesopores accounts for 75% to 100% of the total pore volume.

2. The phosphorus-carbon composite material as described in claim 1, characterized in that, The specific surface area of ​​the phosphorus-carbon composite material is ≥70m². 2 / g, for example 70-120 m 2 / g.

3. A method for preparing the phosphorus-carbon composite material as described in claim 1 or 2, characterized in that, The method includes the following steps: (1) Add carbon materials and phosphorus into the reactor and evacuate the reactor to the first vacuum level; (2) Inject protective gas into the reactor to the second vacuum level; (3) Heat the reactor to the first temperature to evaporate the phosphorus; (4) The material is kept at a first temperature for a first time, and then kept at a second temperature for a second time, so that phosphorus is deposited on the surface and in the pores of the carbon material to obtain the deposited product.

4. The method as described in claim 3, characterized in that, Step (1) has one or more of the following characteristics: The carbon material is selected from one or more of zeolite template carbon, carbon nanotubes, coconut shell carbon, and phenolic resin hard carbon; The phosphorus mentioned is red phosphorus; In the pore structure of the carbon material, micropores account for 80% to 90% of the volume, and mesopores account for 10% to 20% of the volume. The reactor is a high-temperature resistant tube, preferably a high borosilicate glass tube, a quartz glass tube, an aluminosilicate glass tube, or a high-purity alumina tube; The mass ratio of the carbon material to the phosphorus is 1:0.3 to 1:8; The first vacuum level is a relative vacuum of -0.1 to 0 MPa.

5. The method as described in claim 3, characterized in that, Step (2) has one or both of the following characteristics: The protective gas is argon or nitrogen; The second vacuum degree is a relative vacuum degree of -0.1~0.2 MPa.

6. The method as described in claim 3, characterized in that, The method has one or more of the following characteristics: In step (3), the heating rate to the first temperature is 2~5℃ / min, and the first temperature is 400℃~700℃; In step (4), the first time is 1 h to 10 h; In step (4), the second temperature is 200℃~300℃; In step (4), the second time is 10~30 h; Step (4) further includes: after holding at the second temperature for a second time, naturally cooling to room temperature.

7. The method as described in claim 3, characterized in that, The method further includes a cleaning step, which involves cleaning the deposited product obtained in step (4) with a cleaning solution and then drying it; wherein the cleaning solution is one or more of NaOH solution, dilute nitric acid and CS2; wherein the concentration of NaOH in the NaOH solution is 1 mol / L to 3 mol / L, and the mass fraction of nitric acid in the dilute nitric acid is 5% to 10%.

8. The method as described in claim 3, characterized in that, The method for preparing zeolite template carbon in step (1) includes the following steps: (1') Pretreatment of zeolite molecular sieves; (2') Carbon is deposited on zeolite molecular sieves by vapor deposition; (3') Acid washing removes zeolite molecular sieves to obtain zeolite template carbon; Preferably, in step (1'), the zeolite molecular sieve is selected from one of Y-type zeolite, β-type zeolite, LTA-type zeolite and ZSM-5 zeolite; the pretreatment of the zeolite molecular sieve is to heat to 200℃~400℃ in an inert atmosphere, the inert atmosphere being nitrogen or argon, for 1~10 h. Preferably, in step (2'), the vapor deposition includes two stages. In the first stage, the temperature is increased to 500°C to 800°C at 5°C / min in a mixed atmosphere of 10 to 70 sccm carbon source gas and 20 to 70 sccm protective gas for 1 to 10 h. The carbon source gas is one of methane, ethylene, propylene, and acetylene. The protective gas is selected from nitrogen, argon, and an argon / hydrogen mixture, wherein the argon / hydrogen mixture is 2% VOL to 5% VOL H2 and 95% VOL to 98% VOL argon. In the second stage of vapor deposition, the protective gas is switched to a heated atmosphere and the temperature is increased to 700°C to 1200°C at 5°C / min for 1 to 10 h. Preferably, in step (3'), the acid washing is performed by washing away the zeolite template with a mixed solution of 50~200 mL of 0.1~1 M HF and 50~200 mL of 0.1~1 M HCl to obtain zeolite template carbon.

9. A negative electrode sheet or sodium-ion battery, characterized in that, The negative electrode or sodium-ion battery comprises a phosphorus-carbon composite material as described in claim 1 or 2, or a phosphorus-carbon composite material obtained by any one of claims 3-8.

10. Selected from the following applications: (1) The method of any one of claims 3-8 is used to improve the uniformity of phosphorus filling in the pores of carbon materials; (2) The application of the phosphorus-carbon composite material as described in claim 1 or 2 or the phosphorus-carbon composite material obtained by any one of claims 3-8 in improving battery capacity and / or cycle stability.